2022
DOI: 10.5267/j.ijdns.2022.6.005
|View full text |Cite
|
Sign up to set email alerts
|

Mobile government public value model for assessing the public institution’s services: Evidence through the context of Jordan

Abstract: Having a citizen's opinion is considered the most important method to evaluate a public institution's performance. As a contemporary theory regarding public institutions and private organizations, public value theory provides an alternative approach to evaluating organizations' performance. The current research has provided a new insight to assess the Mobile-government applications (m-gov app) by proposing a new model entitled ‘Mobile Government Public Value (MGPV)’ to measure the performance of m-gov apps in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Scott et al (2016) initially instituted the developed theoretical framework for connecting the intention to use specific technology to public value theory in government service settings, relying on three primary attributes: efficiency, effectiveness, and social value. The empirical evidence confirmed that citizens' intention to use mobile services in the government sector is critical in generating or growing public value efficiency, public value effectiveness, and public value social value (Alhanatleh et al, 2022). To fulfill the objectives of this study, the use of MFS depending on cybersecurity awareness and its priors would provide new insights to create public value efficiency, public value effectiveness, and public value social value among public institutions from citizens' perspectives According to above above-mentioned justifications, the following hypotheses will target at identifying the level of public value of using the MFS among citizens of Jordan: Therefore, in accordance with the overall abovementioned justifications, Figure 1 clarifies the variables and hypotheses of the present study.…”
Section: Literature Reviewmentioning
confidence: 61%
See 3 more Smart Citations
“…Scott et al (2016) initially instituted the developed theoretical framework for connecting the intention to use specific technology to public value theory in government service settings, relying on three primary attributes: efficiency, effectiveness, and social value. The empirical evidence confirmed that citizens' intention to use mobile services in the government sector is critical in generating or growing public value efficiency, public value effectiveness, and public value social value (Alhanatleh et al, 2022). To fulfill the objectives of this study, the use of MFS depending on cybersecurity awareness and its priors would provide new insights to create public value efficiency, public value effectiveness, and public value social value among public institutions from citizens' perspectives According to above above-mentioned justifications, the following hypotheses will target at identifying the level of public value of using the MFS among citizens of Jordan: Therefore, in accordance with the overall abovementioned justifications, Figure 1 clarifies the variables and hypotheses of the present study.…”
Section: Literature Reviewmentioning
confidence: 61%
“…Moreover, the intention to use MFS has been measured with four items from Alodat et al (2022). Finally, the endogenous factors (public value dimensions) have been evaluated with 19 items, as in Alhanatleh et al (2022). The measure of a five-point Likert has gradually been scaled for the survey items in the current study from "1 = strongly disagree" to "5 = strongly agree."…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely tested with different control variables and on a variety of subjects such as farmers, students and working professionals (To and Trinh, 2021). It is regarded as a strong and parsimonious model because it has been well-studied and empirically tested with a well-validated inventory of measurable scales across different contexts (Lee et al ., 2020; Alhanatleh et al ., 2022; Merhi et al ., 2021).…”
Section: Theoretical Reviewmentioning
confidence: 99%